Production of microencapsulate glycidyl methacrylate with melamine formaldehyde resin shell materials - Bel, T. (American Institute of Physics Inc., 2016)
This study gives some information about the preparation of Glycidyl Methacrylate (GMA) microcapsules with Melamine Formaldehyde (MF) resin as a shell material (MF-GMA). Melamine formaldehyde resin containing hydroxyl groups was synthesized in the first step. Second step includes the addition of GMA monomer along with Sodium Dodecyl Benzenesulfonate (SDBS) and Polyvinyl Alcohol (PVA) aqueous solution for getting emulsible solution. The resultant MF-GMA microcapsules had good enclosing performance and thermal stability. The characteristic properties and the morphology of microencapsulated Glycidyl Methacrylate were examined by using FTIR analysis and their morphology was investigated by using optical microscope. Â© 2016 Author(s).